Data-Driven Real-Time Pricing Strategy and Coordinated Optimization of Economic Load Dispatch in Electricity Market - Wang, Shunjiang; Zang, Yuxiu; Ge, Weichun; Wang, Aihua; Li, Dianyang; Tang, Jingyi (Frontiers in Energy Research, 2021)
Compared to the step tariff, the real-time pricing (RTP) could be more stimulated for household consumers to change their electricity consumption behaviors. It can reduce the reserve capacity, peak load and of course the electricity bill, which could achieve the purpose of saving energy. This paper proposes a coordinated optimisation algorithm and data-driven real-time pricing strategy in electricity market. First, the electricity price is divided into two parts, basic electricity price and fluctuating price. When the electricity consumption is equal to the average daily electricity consumption, the price is defined as the basic electricity price, which is the clearing electricity price. The consumers electricity data are analyzed. A random forest algorithm is adopted to predict the load data. Optimal adjustment parameters are obtained and the load fluctuation and the fluctuation of the electricity price is further quantified. Secondly, the appliances are modeled. The operation priority is established based on the preferences of customers and the Monte Carlo method is used to form the power load curve. Then, the smart energy planning unit is proposed to optimize the appliances on/off time and running time of residential electrical appliances. An incentive mechanism is used to further standardize the temporary electricity consumption. An improved multi-objective particle swarm optimization algorithm (IMOPSO) is adopted, which adopt the linear weighted evaluation function method to maximize the consumer’ social welfare while minimizing the electricity bill. The simulation proves that the stability of the power grid is improved while obtaining the best power strategy.